P246Cystatin C and hemorheological parameters in the essential hypertension patients. (15th July 2014) - Oschepkova, E; Ageeva, N; Dmitriev, V; Rogoza, A; Titov, V
Abstract: Objective: Cystatin C, an endogenous marker for glomerular filtration rate - kidney function, also correlates with cardiovascular risk factors. At the same time changes of blood fluidity are also one of main risk factors of cardiovascular disorders. The aim of our study was to investigate if it is association Cystatin C with hemorheological parameters of blood in the essential hypertensive patients (EH pts). Design and Methods: 26 EH pts (18M, 8F) grade 1 or 2, av. age 48, 4±2, 4 years with short duration EH (no more 5 years) and without chronic kidney disease (Creatinine level: 84, 7±1, 9 μmol/L, GFR: 114, 9±5, 4 ml/min), 24-h SBP was 140, 8±2, 7 mm.Hg., 24-h DBP was 86, 0 ±2, 6 mm Hg. Cystatin C was defined by a method of turbidimetry on the Architect C 8000 analyzer (Abbot, USA). Whole blood viscosity of native blood and at standard hematocrit =30 at high (128c-1) ν1 and low (0, 95c-1) ν2 shear rates, plasma viscosity (νpl) were measured by a rotational viscometer (Low Shear 30 "Contraverse", Switzerland). Hematocrit (Ht) and aggregation of erythrocytes (ν2/ ν1) were studied also. 24 hour blood pressure monitoring (24-h BPM) was carried out by BPlab (Russia).The statistical analysis was carried out by nonparametric method of Spearman with STATISTICA 6. The data is presented as M±SE. Results: In the whole group EH pts Cystatin C level was 1, 00±0, 02 μg/L, Ht=49, 7±0, 8%, ν1=5, 05±0, 10sPs, ν2=26, 5±1, 2sPs, νpl=1, 51±0, 01 sPs, at standard hematocrit ν1st= 3, 18±0, 02, ν2st 8, 2±0, 4, ν2/ ν1=5, 2±0, 1. Significant association Cystatin C with platelet aggregation (r=0, 49; p<0, 05) and plasma viscosity ν2 (r=0, 46; p<0, 05) were found. We didn't find significant association Cystatin C with other hemorheological parameters. Conclusion: our results confirm a hypothesis of significant influence of Cystatin C on hemorheological properties of blood in EH pts, what can be an additional risk factor for cardiovascular negative events.